Qualitative Analysis of Attitudes Toward Adult-Child Sexual Activity Among Minor-Attracted Persons. Issue 8 (17th November 2018) - Spriggs, Sharron A.; Cohen, Lisa J.; Valencia, Ashley; Yaseen, Zimri S.; Galynker, Igor I.
Abstract: This study uses qualitative methodology to explore narrative responses to a question regarding the harmful versus beneficial effects of adult-child sex on children. Data were gathered from a survey of self-identified minor-attracted persons (MAPs). Two hundred and sixty-seven survey participants provided narrative responses. Results indicated a significant amount of variability in perceptions of harm and of mitigating or aggravating factors. Understanding the subjective perspectives of MAPs, the range of their attitudes, and the issues that they identify as pertinent is critically important for clinical efficacy in the treatment of pedophilia.